2019
DOI: 10.1016/j.cmet.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Dissection of Daily Variance in Exercise Capacity

Abstract: Highlights d Mice and humans show daily variance in exercise capacity d Exercise intensity and clock proteins affect daytime variance in exercise capacity d Exercise elicits distinct daytime muscle transcriptomic and metabolic signature d ZMP, an AMPK activator, is induced by exercise in a daytimedependent manner

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
137
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(157 citation statements)
references
References 59 publications
14
137
6
Order By: Relevance
“…However, it is more well known as a drug that is given to activate AMP kinase, but was recently shown to be endogenously produced by intense endurance exercise (Ezagouri et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is more well known as a drug that is given to activate AMP kinase, but was recently shown to be endogenously produced by intense endurance exercise (Ezagouri et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…AICAR is an intermediate in the synthesis of inosine monophosphate (IMP), reviewed in Daignan-Fornier & Pinson (2012). However, it is more well known as a drug that is given to activate AMP kinase, but was recently shown to be endogenously produced by intense endurance exercise (Ezagouri et al 2019).…”
Section: Differences Between Males and Femalesmentioning
confidence: 99%
“…Exercise is a well-known stimulus that can alter skeletal muscle and organismal physiology. While emerging data have shown potent time-of-day specific outcomes of exercise on skeletal muscle gene expression and metabolism (Ezagouri et al 2019;Gabriel & Zierath, 2019;Sato et al 2019), studies of the potential role of exercise as an environmental time cue for circadian clocks have been limited. Specifically, studies have performed time-of-day exercise interventions and measured both behavioural as well as clock outcomes but all these studies performed repeated exercise training (Edgar & Dement, 1991;Marchant & Mistlberger, 1996;Yamanaka et al 2008;Wolff & Esser, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In many individuals, especially in people with a late chronotype, an advance of the internal circadian rhythm would better align internal rhythms with the environment and with standard social schedules. Recent studies in mice showed that exercise performance, gene transcription, and energy utilization depend on the time of day of exercise (31,32). Clinical studies have conflicting results, but some have shown that morning or early afternoon exercise phase advances, while evening exercise phase delays the internal circadian rhythm (21,(33)(34)(35)(36).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%